Geochemical characteristics and exploration potential of Jurassic coal-formed gas in northwest China - Jian Li; Aisheng Hao; Xuening Qi; Xuan Chen; Jianying Guo; Qigui Ran; Zhisheng Li; Zengye Xie; Xu Zeng; Jin Li; Yu Wang; Ruhong Liu (Journal of Natural Gas Geoscience, 2019)
Jurassic coal-measure strata are widely developed in Northwest China and mainly distributed in the Tarim Basin, Junggar Basin, Qaidam Basin, and Tuha Basin. The Jurassic coal-formed gas resources are abundant. Although the Jurassic strata in Northwest China have similar tectonic and sedimentary environments, the geochemical characteristics of the coal-formed gas formed in Northwest China have both similarities and differences. Therefore, analyzing and summarizing the geochemical characteristics and exploration potential of the coal-formed gas in the Jurassic petroleum systems in different basins are of great significance for searching for different types of coal-formed gases. Through comprehensive comparison and analysis, it is believed that the drying coefficient of Jurassic coal-formed gases in western China present three types: namely the single peak type of wet gas, the double peak type wet gas-dry gas and the single peak type dry gas; the distribution range of δ13C1 is large, corresponding to the sequence of source rocks from low maturity to over-mature; the partial isotopic inversion of C2 and C3 is mainly caused by the mixed source and biological actions; source rock maturity is the main reason causing the geochemical differences of natural gases in different regions. The Jurassic coal-formed gas in Northwest China has large exploration potential, and the exploration degree of structural gas reservoirs is relatively high. The structural-lithological and lithological gas reservoirs, as well as the main exploration reservoir types for Jurassic coal-formed gas in Northwest China; the Jurassic system in the Kuqa Depression of Tarim Basin, Cretaceous-Jurassic system in the southern margin of the Junggar Basin, the Jurassic high maturity coal-formed gas in the Tuha Basin and the Jurassic high maturity–post-mature coal-formed gas in the Qaidam Basin have great exploration potential, which are important exploration fields for Jurassic coal-formed gas in Northwest China in the future. Keywords: Northwest China, Jurassic coal-formed gas, Geochemical characteristics, Exploration potential